Breastfeeding and Birth mode: comparative analysis between elective and in-labor caesarean section. (13th November 2019) - Napolitani, M; Lorenzini, C; Kundisova, L; Crescenzo, F; Alaimo, L; Nante, N
Abstract: Introduction: Evidence in literature suggests that the outcomes of children born by in-labor non-emergency caesarean section (CS) are better if compared to those born by programmed CS. The aim of this work was to evaluate impact of type of CS on neonatal outcomes and breastfeeding. Materials and methods: The cross-sectional study was performed in the Siena province (hospital of Siena and Poggibonsi) during the period January-December 2015. All females that gave birth by CS were included, except those that had emergency CS from severe medical indication (pre-eclampsia/eclampsia, fetal distress, intrauterine growth retardation, etc) or due to multiple pregnancy. The sample was divided in two groups (programmed CS/CS in the presence of labor). The outcome variables were: necessity of hospitalization in neonatal intensive therapy unit (NITU) or resuscitation; weight loss after birth (%), hours passed between birth and first attack to the breast, type of breastfeeding at discharge (exclusive/mixed). The statistical analysis was performed with Stata 12. Results: In total 446 females were included (53.6% programmed CS). Any association between the type of CS and admission to NITU or resuscitation was observed. Among the newborns born by CS in the presence of labor, there was a greater proportion of babies who attached to the breast immediately after birth (82% vs. 71%; p < 0.05) and also those exclusively breastfed at the moment of discharge (71% vs. 60%; p < 0.05). The weight loss was lower in babies born by CS in the presence of labor (8%±1.8; 95% CI 7.7%-8.2% vs. 8.53%±1.7%; 95% CI: 8.3%-8.8%; p < 0.05). Conclusions: Our study confirmed the negative impact of the CS in the absence of labor on the breastfeeding initiation, probably due to incomplete activation of neuroendocrine mechanisms (release of oxytocin; etc). The CS in the presence of labor is more stressful from the organizational point of view, but it helps promotion of health through the facilitation of breastfeeding. Key messages: In-labor non-emergency caesarean section is more physiological and helps to initiate and maintain breastfeeding. The CS in the presence of labor is more stressful from the organizational point of view, but it helps promotion of health through the facilitation of breastfeeding.